O passado e o futuro da pegada hídrica da soja e seus impactos socioeconômicos: a dinâmica espacial da última fronteira agrícola do cerrado no norte-nordeste do Brasil - Santos, João Francisco Severo (Universidade Federal do Tocantins, 2021)
The soybean [Glycine max (L.) Merrill] is currently one of the main food sources in the world scenario and the main export product of Brazilian agriculture. As a consequence of the hegemonic discourse that the increase in scale of commercial agriculture promotes the interiorization of socio economic development, this crop prospered, from the 1970s onwards, in the soils of the Cerrado that, until then, were considered poor for commercial agriculture. Nevertheless, according to the Brazilian Panel on Climate Change, the areas of the Cerrado are very vulnerable, as they are absorbed and the waters that supply three important aquifers and six large Brazilian river basins emerge. In this context, the main objective of this study was to understand the spatial and temporal dynamics of the Water Footprint - WF of soy cultivation in the face of climate change scenarios and its socio-economic impact in the municipalities inserted in the last agricultural frontier of the Cerrado in the North and North-east regions of Brazil. The methodology used was adapted from the protocol proposed by Hoekstra and contemplated the calculation of the different components (green, blue and grey) of the WF of soy production, in its relative (m³/t) and absolute (km³) form, in the near past (1999 - 2018) and in the medium (2049/22050) and long term (2079/2080) future. At the same time, the validation and analysis of the determining climatic factors and models for the estimation of the WF in the past and in the future were performed. Additionally, the social impact of soy production was analysed from the perspective of economic development, as well as income inequality of farming establishments and concentration of productive land in producing and non-producing municipalities. For that purpose, different groups of municipalities were considered according to the time of consolidation of soybean cultivation and its proportion in each municipality's gross domestic agricultural product. Time series were elaborated for the period in order to analyse behavioural trends of climate, production, occupation of productive areas, application of agrochemicals, relative and absolute WF, and its components. Several spatial resolutions were used to locate the micro-regions and municipalities with the highest water consumption for soy production. The results revealed that there was an increase in the average temperature and a small reduction in rainfall accumulated in the past period, but this did not significantly affect the relative WF, since the green and blue components suffered a decrease due to increased crop productivity over time. Only the grey component showed a significant increase, regardless of the pollutant or legislation used as parameter for the calculation. Spatially, the micro regions near the transition from the Cerrado to the Caatinga showed the greatest need and shortage of water in the past and in the future. The micro-regions near the transition Cerrado/Amazonia were the least affected by the increase in temperatures and did not present water scarcity, with the lowest WFs. In the socio-economic aspect, the soybean producing municipalities are the ones that present the greatest growth and economic development, but without expressive gains in job generation and income distribution. Even the municipalities with soybean production over 30 years had lower composite health indicators than the other categories. Moreover, income inequality in agricultural establishments increased between 2006 and 2017. During that period, the concentration of agricultural land increased only in municipalities with 10 years or less of soy production. In summary, evidence shows that soy production in the last agricultural frontier of the Cerrado consumes a lot of fresh water, participates in local climate changes and is vulnerable to future climate changes, besides contributing little to the development of municipalities and reduction of rural inequalities.